2020
DOI: 10.1001/jamanetworkopen.2020.20977
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported Cannabidiol (CBD) Use for Conditions With Proven Therapies

Abstract: IMPORTANCE Use of cannabidiol (CBD) has markedly increased in the past 5 years, concurrent with marketing claims that over-the-counter CBD can be used to treat almost any health condition. However, the reasons why individuals use CBD remain unclear. OBJECTIVE To assess whether individuals are using CBD for diagnosable conditions that have evidence-based therapies. DESIGN, SETTING, AND PARTICIPANTS This case series assessed claimed treatment applications reported by CBD users in public testimonials shared on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 15 publications
1
42
0
Order By: Relevance
“…We identified two vape shops that made explicit health claims about CBD’s effectiveness for treating anxiety, inflammation, pain, and stress, which are not FDA-approved uses of CBD. The claims we identified are consistent with findings of a recent analysis of user testimonials on the largest social media forum devoted to discussing CBD that found that psychiatric (e.g., anxiety) and orthopedic (e.g., joint pain) conditions were the most commonly reported medical reasons for using CBD [ 9 ]. Such unsubstantiated claims may increase use of CBD products, prolong illnesses with existing effective treatments, and expose consumers to both known and unknown health risks without conferring any of the purported benefits.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We identified two vape shops that made explicit health claims about CBD’s effectiveness for treating anxiety, inflammation, pain, and stress, which are not FDA-approved uses of CBD. The claims we identified are consistent with findings of a recent analysis of user testimonials on the largest social media forum devoted to discussing CBD that found that psychiatric (e.g., anxiety) and orthopedic (e.g., joint pain) conditions were the most commonly reported medical reasons for using CBD [ 9 ]. Such unsubstantiated claims may increase use of CBD products, prolong illnesses with existing effective treatments, and expose consumers to both known and unknown health risks without conferring any of the purported benefits.…”
Section: Discussionsupporting
confidence: 87%
“…While the pharmacological profile of CBD suggests that additional therapeutic applications of CBD could eventually be approved by the FDA, the public may already perceive that CBD is an effective therapeutic for many health conditions that it may never be approved to treat [ 8 ]. This is of particular concern when patients are substituting CBD for other proven effective treatments–prolonging illnesses that could otherwise be alleviated [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBD use is not devoid of health risks; known risks include liver damage, adverse effects on the male reproductive system, potential drug interactions that may be associated with adverse events or diminished efficacy of approved therapies, and additional unknown health risks. However, the pharmacology of CBD has not been well studied; thus, little is known about both the potential therapeutic benefits and the hazards of short- or long-term use (Leas et al 2020 ). According to our study, restlessness was the only mild side effect seen in some patients which was resolved on making some doses adjustments.…”
Section: Discussionmentioning
confidence: 99%
“…Unsupported claims pose a concern for those using CBD for medical purposes, who may accept the accuracy of such claims and spend significant amounts of money on these products for potentially little benefit [31][32][33]. This is especially concerning in situations when CBD is purchased to improve or treat life-threatening illnesses among patients who may forego evidence-based treatments [34][35][36]. The spread of unproven and, in many cases, false claims, contributes to the spread of misinformation.…”
Section: Discussionmentioning
confidence: 99%